Anthropological foundations of Polish Penal Law in the light of the 1997 Constitution of the Republic of Poland - Ciepły, Filip (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
When making penal law regulations, the legislator is faced with axiological choices of tremendous impact, hence it should take into consideration the moral conditions that are inherent to the specific civilisation and culture, particularly interpreted from constitutional axiology. In the doctrine of penal law and penal sciences that aspire to influence the content of penal legislation, the perspective of constitutional values, principles and norms should always be taken into account. However, the constitutional context does not only offer strict and express legal rules, precisely formulated guarantees, imperatives and prohibitions, constitutional or competence-related provisions but also generally worded optimising norms and, often only implicit preferences, assumptions and axiological views of the author, among them the vision of human nature. The specific anthropological concept that the constitution-maker has assumed as the axiological basis of its law-making decisions proves to be heterogeneous and becomes a necessary reference point for various law-making and law-applying bodies, all recipients of legal norms, and also the representatives of scientific disciplines recommending changes to the law.The anthropological stance adopted in the Constitution can be inferred primarily from the principle of human dignity as well as from the foremost position of the personal freedom of the individual in the hierarchy of constitutional values or from the interpretation of the constitutional concept of common good. The principle of human dignity entails the axiomatisation of the normative content of the Constitution. The Constitution of the Republic of Poland, in its Article 30, does not aspire to re-invent the concept of the human being or prioritise specific rights and freedoms but only confirms that they exist and obliges public bodies to respect and protect them. The analysis of the content of the Constitution of the Republic of Poland reveals that it is founded on the personalistic concept of a human being. This indeterministic concept implies that the individual takes rational and free choices and socially relevant decisions manifested in their actions and is subject to liability, including penal liability, based on these actions. This is relevant to the definition of the paradigm of expert assessments of penal law and to the legislative effort.Under effective constitutional law, it is impossible to develop a system of penal law response based on such anthropological concepts as behaviourism, determinism, post-humanism, anti-humanism, trans-humanism, biotechnology, trans-species approaches, etc. The idea of the rejection of the subjective nature of a human being and departure from the classic rules of penal liability based on the perpetrator’s actions and guilt are out of the question. These notions should be interpreted in the light of personalistic anthropology. Any concepts that rationalise penal sanctions exclusively on the grounds of protection of public safety or crime prevention which make penal liability instrumental and objectify perpetrators are in conflict with constitutional axiology. Moreover, constitutional anthropology cannot endorse solutions that implement a strictly behavioural vision of crime response, that is, one in which the application of penal sanctions is understood as a kind of social engineering or correctional tool separated from liability. The perpetrator of a prohibited act cannot be subject to interventions regarded as forced therapy or psychotechnical correction of non-conformist attitudes and pathological personality. It is also unacceptable to attempt to treat animals or artificial intelligence as subjects of law or making them fall under penal liability.
Keywords: aksjologia prawa karnego; paradygmaty nauk karnych; antropologia konstytucyjna; etyczne założenia porządku prawnego; szkoły kryminologiczne